Documentary representation for access and visibility to graffiti - Lima, Fabio Rogerio Batista [UNESP]; Santos, Placida Leopoldina Ventura Amorim da Costa [UNESP]; Zafalon, Zaira Regina (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2022)
The artistic production is one of the vestiges of the material and immaterial cultural heritage left by human beings throughout their existence. The artistic manifestations are also on the walls of cities, places that enshrine the ephemeral nature of graffiti, where their surfaces are changed and whitewashed frequently. Due to that, the question is: how can graffiti persistence be guaranteed as an information resource and, consequently, attest its access and visibility to future generations? As a general objective, it is proposed a graffiti document representation model, oriented to access and visibility, with descriptive, thematic, cultural, space-temporal, and ideological characteristics. Its scope is defined as specific objectives: to discuss graffiti and its ephemeral aspects, including on account to evaluate methods and instruments that provide conditions for the persistence of graffiti and its identification as an information resource. This research, with a qualitative and applied approach, seeks descriptive and exploratory objectives and makes the use of bibliographic and documentary procedures. As contributions include: discussion of information resources and documentary representation as the object of Information Science, graffiti as a cultural manifestation, the ephemerality of street art, with emphasis on graffiti and the consecration of information resources as material cultural goods.
Keywords: Graffiti; Graffiti documentation; Descriptive representation of image information resources; Cultural heritage